Assessing the role of IKCa channels in generating the sAHP of CA1 hippocampal pyramidal cells. Issue 4 (3rd July 2016) - Turner, Ray W.; Asmara, Hadhimulya; Engbers, Jordan D. T.; Miclat, Jason; Rizwan, Arsalan P.; Sahu, Giriraj; Zamponi, Gerald W.
ABSTRACT: Our previous work reported that KCa3.1 (IKCa) channels are expressed in CA1 hippocampal pyramidal cells and contribute to the slow afterhyperpolarization that regulates spike accommodation in these cells. The current report presents data from single cell RT-PCR that further reveals mRNA in CA1 cells that corresponds to the sequence of an IKCa channel from transmembrane segments 5 through 6 including the pore region, revealing the established binding sites for 4 different IKCa channel blockers. A comparison of methods to internally apply the IKCa channel blocker TRAM-34 shows that including the drug in an electrode from the onset of an experiment is unviable given the speed of drug action upon gaining access for whole-cell recordings. Together the data firmly establish IKCa channel expression in CA1 neurons and clarify methodological requirements to obtain a block of IKCa channel activity through internal application of TRAM-34.